MINUTE PATELLOGASTROPODS (MOLLUSCA, LOTTIIDAE) FROM THE MIDDLE MIOCENE OF PARATETHYS - Anistratenko O.; Anistratenko V. (My University, 2007)
The protoconch and teleoconch morphology of lottiid patellogastropods that inhabited the Central and Eastern Paratethys in the Badenian and Sarmatian are described and illustrated. Eleven species belonging to the genera Tectura, Blinia, Flexitectura and Squamitectura are considered as valid: Tectura laevigata (EICHWALD, 1830), T. compressiuscula (EICHWALD, 1830), T. zboroviensis FRIEDBERG, 1928, T. incognita FRIEDBERG, 1928, Blinia angulata (D'ORBIGNY, 1844), B. pseudolaevigata (SINZOV, 1892), B. reussi (SINZOV, 1892), B. sinzovi (KOLESNIKOV, 1935), Flexitectura subcostata (SINZOV, 1892), F. tenuissima (SINZOV, 1892), and Squamitectura squamata (O. ANISTRATENKO, 2001). The type material of species introduced by W. FRIEDBERG (1928) is revised and lectotypes are designated for T. zboroviensis and T. incognita. The taxonomic status and position of this group of species is discussed. Data on palaeogeographic and stratigraphic distribution, variability and the relationships of Middle Miocene Lottiidae GRAY, 1840 are presented.
Keywords: BLINIA; FLEXITECTURA; LOTTIIDAE; MIOCENE; PARATETHYS; PATELLOGASTROPODA; SHELL MORPHOLOGY; TAXONOMY; TECTURA; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен